THE CHARACTERISTICS OF SELF SIN IN CERAMIC FINE ARTS - Admiral Akhir Abdillah; Novita Wahyuningsih (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
Sin is an activity that violates God’s law provision. Unfortunately, sin cannot be separated from human. The categorization of sin characteristics by Catholic church in the glory era of Christianity called “Seven Deadly Sins” gives information to recognize sin characteristics that are often experience by oneself. Seven Deadly Sins and other library sources trying to explain about sin from several religious views in Indonesia bring out new comprehension about sin. Based on the new comprehension about sin, the ceramics were created. The main material used was clay from Bentangan, Klaten, Jawa Tengah that had been processed so it had better endurance level of temperature. The process of creation used the techniques of hand-building, pinch, and solid mold. Decoration used intaglio, camelo, and kerrawang ornaments while ceramic colorization used the technique of under-glaze firing. The ceramic artworks of “the characteristics of self sin” series have the hope that these artworks contain creative and educative values, and they also function as the warning that there are sin characteristics threatening us in our daily life